Innovation in precision fermentation for food ingredients - Augustin, Mary Ann; Hartley, Carol J.; Maloney, Gregory; Tyndall, Simone (Critical reviews in food science and nutrition, 2024)
A transformation in our food production system is being enabled by the convergence of advances in genome-based technologies and traditional fermentation. Science at the intersection of synthetic biology, fermentation, downstream processing for product recovery, and food science is needed to support technology development for the production of fermentation-derived food ingredients. The business and markets for fermentation-derived ingredients, including policy and regulations are discussed. A patent landscape of fermentation for the production of alternative proteins, lipids and carbohydrates for the food industry is provided. The science relating to strain engineering, fermentation, downstream processing, and food ingredient functionality that underpins developments in precision fermentation for the production of proteins, fats and oligosaccharides is examined. The production of sustainably-produced precision fermentation-derived ingredients and their introduction into the market require a transdisciplinary approach with multistakeholder engagement. Successful innovation in fermentation-derived ingredients will help feed the world more sustainably.